An annotated bibliography of popular archaeological writing in South Africa - Wahl, E. J.; Mazel, A. D. (Southern African Humanities, 2021)
To cite this article: Wahl, E. J. & Mazel, A. D. 1995. An annotated bibliography of popular archaeological writing in South Africa. Natal Museum Journal of Humanities 7: 51-85.